한반도에 영향을 미친 과거 태풍 기반의 가상시나리오를 적용한 폭풍해일 모의: 폭풍해일 및 월파 체적 분석 - 진호영; 황태건; 김현정; 민병일; 이우동; Jin, Hoyeong; Hwang, Taegeon; Kim, Hyeon-Jeong; Min, Byung-Il; Lee, Woo-Dong (Journal of Korea Water Resources Association, 2024)
This study investigates the storm surge risks and vulnerabilities along Jeju Island and the southern coast of the Korean Peninsula by synthesizing historical typhoons and constructing hypothetical scenarios. The validated finite element method-based Advanced CIRCulation (ADCIRC) model was employed to simulate storm surges under various scenarios. We analyzed the maximum storm surge heights, time-series waveforms, and volume ratios across 67 locations, focusing on Jeju Island and the southern and southeastern coasts. The results showed that the Maemi-S2/S3 scenario, where Typhoon Maemi reaches its peak strength, resulted in significantly higher storm surge heights, especially in bay areas. Sarah-S2 and Sarah-S3 scenarios also produced elevated surge heights, while Hinnamnor-S2/S3 scenario recorded lower surge heights overall but still posed risks in certain coastal bays. The time-series analysis revealed that storm surge volume ratios increased significantly in the Maemi-S2/S3 scenario, particularly along the southeastern coast, which had suffered significant damage from Typhoon Maemi, with volume ratios 2.89 times higher than in the Maemi-S1. Additionally, when considering a 1-meter coastal barrier height, the overtopping volume at locations with storm surge heights above 2 meters was 6.66 times greater in the Maemi-S2/S3 scenario compared to Maemi-S1. These findings highlight that surge height cannot adequately assess storm surge risk alone, as overtopping volumes play a critical role in coastal inundation. 본 연구는 과거 한반도에 큰 피해를 입힌 태풍들을 합성하여 가상시나리오를 구성하고, 이를 통해 제주도와 남해안의 폭풍해일 위험성과 취약성을 조사하였다. 검증된 유한요소법 기반의 ADCIRC (Advanced CIRCulation) 모델을 활용하여 다양한 시나리오에서 폭풍해일을 모의하였다. 제주도, 서남해안, 동남해안의 67개 지점을 대상으로 최대 폭풍해일고, 시간파형, 체적비 등을 분석한 결과, 태풍 매미가 최강 세력일 때 상륙하는 Maemi-S2/S3 시나리오에서는 만 지역에서 특히 높은 해일고가 발생하였으며, Sarah-S2와 Sarah-S3 시나리오에서도 비슷한 경향을 보였다. 반면, Hinnamnor-S2/S3 시나리오는 전반적으로 해일고가 낮았으나, 일부 지역에서 높은 해일고를 기록했다. 태풍 매미에 의한 해일피해가 심각했던 동남해안에서 Maemi-S2/S3 시나리오의 체적비는 Maemi-S1 대비 2.89배 증가하였으며, 호안높이 1 m를 고려했을 때 2 m 이상의 해일고를 나타낸 지점에서는 월파 가능 체적비가 Maemi-S1 대비 6.66배로 크게 증가한 것으로 나타났다. 본 연구 결과는 해일고뿐만 아니라 월파 가능 체적이 동남해안 침수 피해 예측에 중요한 요소임을 확인하였다.